Bathymetric control of warm ocean water access along the East Antarctic Margin. Issue 17 (7th September 2017) - Nitsche, F. O.; Porter, D.; Williams, G.; Cougnon, E. A.; Fraser, A. D.; Correia, R.; Guerrero, R.
Abstract: Observed thinning of the Totten Glacier in East Antarctica has cast doubt upon the stability of the East Antarctic Ice Sheet. Recent oceanographic observations at the front of the Totten Ice Shelf have confirmed the presence of modified Circumpolar Deep Water (mCDW), which likely promotes enhanced melting. Details of how this water accesses the shelf remain uncertain. Here we present new bathymetry and autumnal oceanographic data from the outer continental shelf, north of the Totten Glacier, that show up to 0.7°C mCDW in a >100 km wide and >500 m deep depression within the shelf break. In other parts of East Antarctica, a shelf break bathymetry shallower than 400 m prevents these warmer waters from entering the shelf environment. Our observations demonstrate that detailed knowledge of the bathymetry is critical to correctly model the across‐shelf exchange of warm water to the various glaciers/ice shelves of Antarctica for future sea level prediction. Key Points: A large pool of warm modified Circumpolar Deep Water has been identified on the outer continental shelf near the Totten Glacier Shelf break bathymetry varies from 300 to 600 m depth along the East Antarctic Margin with a deeper section offshore Totten Glacier Access of modified Circumpolar Deep Water along the East Antarctic Margin is in part controlled by shelf break depth